2014
DOI: 10.1111/pme.12360
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Bias Toward Negative Information in Patients with Fibromyalgia Syndrome

Abstract: The study provides evidence of emotionally driven selective attention in FMS. Attentional bias to negative information may play an important role in the vicious circle between negative affective state and pain augmentation. In the management of FMS pain, strategies aiming at conscious direction of attention may be helpful, e.g., imagery techniques or mindfulness training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 51 publications
4
65
0
Order By: Relevance
“…In future research, self-report scales, for example concerning emotional self-regulation or affective styles, as well as experimental paradigms addressing emotion processing, could be applied for this purpose. 22,30,53,57 In addition, relationships between interoception and pain experience should also be explored. Another limitation concerns results from our use of a female-only sample, which restricts the generalizability of the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In future research, self-report scales, for example concerning emotional self-regulation or affective styles, as well as experimental paradigms addressing emotion processing, could be applied for this purpose. 22,30,53,57 In addition, relationships between interoception and pain experience should also be explored. Another limitation concerns results from our use of a female-only sample, which restricts the generalizability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…[54][55][56] By extension, proneness to negative emotions may exacerbate the vicious circle between aversive mood states and clinical symptoms including hyperalgesia. 57 Somatosensory amplification may be another factor mediating the association between interoceptive awareness with fibromyalgia. As stated in the Introduction, it has been demonstrated that somatosensory amplification correlates negatively with heartbeat perception performance, 18 whereas increased levels of somatosensory amplification have been reported in FMS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The anhedonia bias hypothesis suggests that patients with depression and patients with chronic pain might be less sensitive to reward, which entails that their attentional system might not adequately respond to rewarding (emotional) stimuli ( 1 , 16 ). Moreover, earlier findings in patients with chronic pain from a different paradigm showed an attentional bias for negative information ( 20 ) and evidence from depression research has demonstrated that adults with depression show attentional biases for dysphoric emotional stimuli, including preferred early orienting and maintenance on them, while maintenance on positive stimuli is reduced ( 15 , 16 ). Therefore, we expected that CP and DC showed facilitated orienting to and longer maintenance on negative emotions (sad faces), while less orienting to and maintaining on positive emotions (happy faces).…”
Section: Introductionmentioning
confidence: 92%
“…Dysfunctional processing of positive and negative emotional information might also play a role in development and maintenance of chronic pain. Few studies have investigated attentional processing of emotional content in chronic pain ( 19 21 ); a recent study reports alterations of emotional and attentional information processing in patients with fibromyalgia ( 21 ), and another study found an attentional bias for negative emotional words in fibromyalgia patients based on the Stroop task ( 20 ). Rossello et al ( 21 ) presented video tours through an external environment under induced pleasant, unpleasant, or neutral affective state and assessed different psychophysiological measures in response to these environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation